The study of genotoxicity and immunotoxicity in workers occupationally exposed to cyanide - Haleem, Azhar M.; Hussein, Nehia N. (Toxicology and environmental health sciences, 2024)
Object Workers are exposed to a wide range of organic and inorganic pollutants during their work, which may cause them serious health damage related to occupational exposure, depending on the type of exposure, its duration, and the type of safety measures applied in the workplace. The current study aimed to determine occupational exposure to inorganic cyanide compounds in automotive painting workshops, determine immunotoxicity and genotoxicity, and compare the results with those of a non-exposed group. Method Seventeen male works in automotive painting distributed in ten workshops within Baghdad, Iraq, were included. They were divided into two age groups (22–33) and (34–44) years, with a main age of 33.116.4. Result The result of immunological and cytogenetic studies and the concentration of cyanide in plasma compared with a non-exposed group of the same age T-lymphocyte subgroup rates (CD4+, CD3+, CD16+, CD8+, CD56+, and natural killer (NK) cells), as well as genotoxicity, were measured via the micronucleus (MN) assay and Total Chromosomal Aberrations (TCAs). The difference between the two groups (5.7 MN/250 cells) and the control group (1.35 MN/250 cells) was statistically significant ( P 0.05), and this increase corresponds to the incidence of Total Chromosomal Aberrations (TCAs), which was 0.39 in the exposed group and 0.11 in the control group. Plasma-thiocyanate (P-SCN), a marker of cyanide exposure, was detected in the plasma and found to be substantially higher (0.54 M) when compared to non-exposed subjects (P 0.05). Conclusions The immunological and cytogenetic indicators showed a clear perception of the extent of damage that may be caused to the genetic material upon permanent exposure to mono-cyanides. However, we need more studies and assessments to find out whether the effect of cyanide is cumulative or immediate and has only an acute toxic effect, or if it is chronic at low concentrations and sub-lethal dose.